Pengaruh Pengetahuan Investasi, Motivasi Investasi Dan Teknologi Informasi Pada Minat Berinvestasi Saham Di Masa Pandemi Covid-19 (Studi Kasus Pada Mahasiswa FEB UNISMA) - Adnan Abdul Khobir; Ronny Malavia Mardani; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe COVID-19 pandemic began to be detected in Indonesia in March 2020, which had a negative impact on various aspects of life. Like; education, office work, business transactions to investment in the capital market. However, with all the negative impacts and limitations during the Covid-19 pandemic, it has actually increased the number of investors in the capital market. By utilizing information technology, securities companies provide facilities in accessing information about investments and transactions with the aim of making it easier for students like students to invest. With such situations and conditions, it is hoped that it will increase student interest in investing. So the reason for this research is to find out how far the influence of investment science, investment motivation, and information technology on the investment interest of FEB UNISMA students. The research technique used in this research is quantitative, with the type of research being a description of the data obtained through questionnaires. The notes obtained from the questionnaire were then processed into SPSS usage with a sample of 85 students The data obtained were then processed and tested for validity, reliability, normality, multicollinearity, heteroscedasticity, then F test and t test and R2 test using SPSS V26. The results of these observations show that investment knowledge has an impact on student investment interest, investment motivation has an impact on student investment interest, and information technology has an impact on student investment interest. Keywords:. Investment Knowledge, Investment Motivation, Information Technology, Investment Interest